Social framing effects: Preferences or beliefs? - Ellingsen, Tore; Johannesson, Magnus; Mollerstrom, Johanna; Munkhammar, Sara (Games and economic behavior, 2012)
In an otherwise neutrally described Prisonersʼ dilemma experiment, we document that behavior is more likely to be cooperative when the game is called the Community Game than when it is called the Stock Market Game. However, the difference vanishes when only one of the subjects is in control of her action. The social framing effect also vanishes when the game is played sequentially. These findings are inconsistent with the hypothesis that the Community label triggers a desire to cooperate, but consistent with the hypothesis that social frames are coordination devices. More generally, our evidence indicates that social frames enter peopleʼs beliefs rather than their preferences. ► We present three theories for why social framing, such as the mere naming of the game, may affect behavior. ► We conduct three Prisonersʼ Dilemma experiments. ► The evidence indicates that social framing primarily affects beliefs, not preferences.